Evaluation of the Reliability and Quality of YouTube Videos about Insulin Injection in Children - Banu Turhan (Düzce Tıp Fakültesi Dergisi)
Aim: Social media platforms, especially YouTube, have become indispensable channels where patients apply for information on medical issues. This study aimed to evaluate the reliability and quality of videos on YouTube about insulin injection in children.Material and Methods: The first 100 videos with the search “insulin injection in children” were analyzed. The distribution of video types, viewing rates, like ratios, number of comments, and video power indexes (VPI) were recorded. The content qualities were assessed by the global quality scale (GQS), modified DISCERN score, the Journal of the American Medical Association (JAMA) benchmark score, and the patient education materials assessment tool for audio/visual (PEMAT-A/V) materials.Results: Forty-seven (47%) videos were analyzed finally. The median score of the GQS was 4, modified DISCERN and JAMA was 3. The median PEMAT A/V understandability and actionability scores were 84 and 75. Videos by professionals were found to have better results than the non-professional (p